The Gray Ghost - Cussler, Clive; Cussler, Clive & Burcell, Robin; Brick, Scott (New York, NY : Penguin Audio, 2018)
The grandson of a man who was wrongly accused of stealing a recovered Rolls Royce prototype a century earlier hires husband-and-wife team Sam and Remi Fargo to solve the mystery and clear his grandfathers name.
Keywords: Adventure fiction; Suspense fiction; Audiobooks